Analisa Pengelolaan Layanan IT Insiden pada PT. XYZ - Zulkarnain zulkarnain (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2020)
XYZ is an electronics assembly industry company on Batam Island. The company has utilized information technology support to support the company's business activities. Utilization of information technology as a whole, starting from the HRD, Finance, Planning, Logistics, Development, Quality and Operation. The company's dependence on the availability of information technology support is very high. So that the necessary operational information technology that is stable and able to provide a quick reaction in the event of a disruption or incident. For this reason, the writer tries to analyze IT Incident management, whether the service currently provides benefits to the company. To find out the analysis, the author will use an approach that refers to the concept of governance that has been recognized or has world standards. From the results of the analysis, the company can make the right decision, whether the IT incident management has been running well and continues to be maintained, or needed some improvement, with the hope that it can increase company productivity. High hopes that the results of this writing will not only benefit PT. XYZ, but it is also useful for other companies, who want to use IT incident management in implementing the company.